Equivalence theorem for generalized dependencies in relational databases - Nguyen, Xuan Huy (Trường Đại học Đà Lạt, 2014)
In this paper, we present some new results related to the differential dependencies in relational databases. The main contributions are the following: 1. To introduce a new concept of generalized differential dependencies. 2 . To claim and proof the equivalence theorem of consequences in the world of all relations, the word of two-tuple relations and propositional logic for the generalized differential dependencies. 3. To show an equivalence between generalized positive Boolean dependencies and generalized differential dependencies.